Model Pembelajaran PBL untuk Penguatan Critical Thinking Skills Siswa pada Materi Tata Surya: Studi Internasional di Kamboja - Ismail Arafat; Hadi Purwanto; Neng Sholihat; Berry Kurnia Villmala (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to examine the effect of the Problem Based Learning (PBL) model on improving students' critical thinking skills in the solar system material at Ma'had An-Ni'mah Al-Islamiyah, Phnom Penh, Cambodia. The method used was a pre-experimental design with a one-group pre-test post-test, involving 12 students as the sample. Data were collected through critical thinking tests, student response questionnaires, and documentation. The results showed a significant improvement in students’ critical thinking skills, with the average pre-test score of 30% increasing to 80% on the post-test. N-Gain analysis yielded an average of 0.837 (83.70%), with all students categorized as high. The hypothesis test revealed a t-value of -64.891 and a p-value of 0.000 (< 0.05), indicating a significant difference between pre-test and post-test scores, with an average increase of 51.417 points. Students also gave highly positive responses to the implementation of the PBL model. In conclusion, the PBL model is effective in improving students’ critical thinking skills in learning about the solar system. Keywords: Critical Thinking, Education, Learning Model, Problem Based Learning, Students